2018
DOI: 10.1037/pha0000191
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and readiness for tobacco cessation among nicotine dependent postmenopausal females: A pilot study.

Abstract: Despite considerable health risks due to lower levels of estrogen production and the compounding antiestrogenic effects of nicotine, postmenopausal females continue to smoke. These females face significant barriers to cessation, including negative affect, weight concerns, and menopausal symptom severity. The current pilot study explored the effect of negative affect, weight concerns, and menopausal symptom severity on motivation and readiness to quit smoking. Eighteen postmenopausal smokers were randomized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Motivational interviewing is widely implemented in primary care and other medical settings, and women with alcohol-related illnesses may be encouraged to reflect on drinking patterns and make behavioral changes, especially since older women are less likely to seek treatment for alcohol use in specialized treatment settings [5]. This is further supported by evidence suggesting the assessment of smoking behaviors and health (e.g., lung age and blood pressure) was related to a decrease in cigarettes per day in a previous study of postmenopausal women [22]. Thus, such intersection with medical providers may be beneficial in assisting older women in cutting down or stopping alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Motivational interviewing is widely implemented in primary care and other medical settings, and women with alcohol-related illnesses may be encouraged to reflect on drinking patterns and make behavioral changes, especially since older women are less likely to seek treatment for alcohol use in specialized treatment settings [5]. This is further supported by evidence suggesting the assessment of smoking behaviors and health (e.g., lung age and blood pressure) was related to a decrease in cigarettes per day in a previous study of postmenopausal women [22]. Thus, such intersection with medical providers may be beneficial in assisting older women in cutting down or stopping alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…34 This highlights the need to develop novel interventions to increase motivation to quit smoking and improve cessation outcomes among this population. Previous research has shown that menopausal symptom severity, including somatic menopausal symptoms (eg sweating, hot flashes, cardiac complaints), was related to increased motivation to quit smoking 35 ; thus, evaluating one's health and menopausal symptomatology may increase motivation to quit smoking among postmenopausal women. 35 In future work, it may be beneficial to incorporate health evaluation into motivational-based interventions with this population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that menopausal symptom severity, including somatic menopausal symptoms (eg sweating, hot flashes, cardiac complaints), was related to increased motivation to quit smoking 35 ; thus, evaluating one's health and menopausal symptomatology may increase motivation to quit smoking among postmenopausal women. 35 In future work, it may be beneficial to incorporate health evaluation into motivational-based interventions with this population. In addition, addressing other potential barriers to cessation, including psychosocial stress may be advantageous.…”
Section: Discussionmentioning
confidence: 99%